Identity verification using shape and geometry of human hands. Issue 2 (1st February 2015) - Sharma, Shefali; Dubey, Shiv Ram; Singh, Satish Kumar; Saxena, Rajiv; Singh, Rajat Kumar
Highlights Shape and geometry features are encoded from contour of the hand only. Robust preprocessing is introduced to cope with the noise and disjoint fingers. Hand orientation and finger registration is applied to provide more flexibility. Two level score fusion is adopted to enhance the verification performance. Promising results are obtained over contact and contactless (IITD) datasets.